Preparation of hydroxyapatite nanofibers by using ionic liquids as template and application in enhancing hydrogel performance - Ren, Xiuli; Liang, Zepeng; Zhao, Xingjun (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Hydroxyapatite (HAP or HA) nanofibers are very attractive in the field of biomedical engineering. However, templates used for preparing HAP nanofibers are usually hydrophobic molecules, like fatty acid and/or surfactants, which are difficult to remove and potentially toxic. Therefore, it is important to develop a green approach to prepare HAP nanofibers.Methods: Imidazolium based ionic liquids (ILs) were used as template to control the crystallization of HAP. The obtained HAP nanofibers were composited into PVA-Alg (polyvinyl alcohol-sodium alginate) hydrogel (HAP@H). The rheological performance, stretching, and compression properties were tested. SEM (scanning electron microscope), HRTEM (high resolution transmission electron microscope), XRD (high resolution transmission electron microscope), FT-IR (fourier transform infrared), and DSC (differential scanning calorimetry) were adopted to characterize the morphology, size, crystallographic orientations and phase of HAP@H.Results: HAP nanofibers with length of ~ 50 µm were harvested. The DSC results proved that water loss temperature increased from 98°C (for pure hydrogel) to 107°C (for HAP@H). And HAP@H hydrogel presents much better porous structure, tensile performance, and compressive performance than that of pure hydrogel.The morphology, size, and the growth direction of HAP could be modulated easily by altering the alky chain length of ILs' cations. This possibly due to face-specific adsorption of imidazolium moieties on HAP nanocrystals. The enhancing performance of HAP@H probably due to the composited highly oriented HAP nanofibers.